What drives OFDI? Comparative evidence from ASEAN and selected Asian economies - Ahmad, F. (Emerald Group Publishing Ltd., 2018)
Purpose: The purpose of this study is to examine the factors that are influential on outward foreign direct investment (OFDI). A sample of four Association of Southeast Asian Nations (ASEAN) countries is compared with dominant Asian economies during 1981-2013. Design/methodology/approach: The authors used time series data for analysis. An econometric model using ordinary least squares, with a series of complementary tests, was estimated for every country to determine the variables affecting OFDI. Findings: The results depict that exchange rates, income and human capital affect the OFDI of most of the countries in the sample. For comparatively advanced and dominant economies (i.e. China, Japan, South Korea and India), openness is the most influential variable, whereas income levels and exchange rates are dominant factors in case of ASEAN economies. Overall, different types of endowments have a different impact for every country. Originality/value: Previous studies have primarily examined advanced countriesâ OFDI. This work adds to the literature by focusing on ASEAN economies and by making a comparison with the dominant Asian economies. Furthermore, the validity and stability of the model is tested with a series of specification tests. In this way, this work is a useful source of information for every stakeholder. Â© 2018, Emerald Publishing Limited.